Determinação do coeficiente de transferência de cargas nas fundações de silos verticais cilíndricos de base semi-V - Fank, Marivone Zanella (2010)
Engineering structures are designed according to the imposed stress. In the case of silos, there is not a Brazilian standard regulation to prescribe their projects and actions. This limitation leads designers to use the foreign standards requirements which, however, differ from one another. This paper shows the evolution of knowledge about the subject, and also aims to experimentally determine the load distribution on vertical cylindrical silos foundations, getting the load transfer coefficient to its bottom and ring, in order to contribute to a better understanding of load distribution for the improvement of these structures design. To conduct the study, four piles on a prototype silo ring located in the Industrial Park C. Vale - Cooperativa Agroindustrial Ltda in Palotina, Paraná, Brazil, were instrumented by using pressure cells. The cell readings were performed by automatic data acquisition during the phases of corn loading, unloading and storage. The results of this research allow the following conclusions: there is a difference between the transferred load and the 30% coefficient usually used in projects. This index showed consistent with the average loads in piles until the silo gets loaded with 50000 kN, which corresponds to 64% of full load. Thereafter, the transference coefficient raised, reaching 50%. Moreover, the observed loads on the instrumented piles were unevenly shown, in other words, the loading on the piles were different, reaching maximum loads of 800, 845, 520 and 600 kN, corresponding to coefficients of 47, 50, 30, and 35%, respectively. The different magnitudes of the loads on piles are associated with the measured values of the settlements, which were high in the foundations located on the tunnel alignment, exceeding 40 mm. Each individual pile behavior identifies the need for detailed coefficients analysis adopted in calculations to avoid structural problems.